African faculties of agriculture within an expanding university sector - Osiru, Moses; Nampala, Paul; Ekwamu, Adipala (International Food Policy Research Institute, 2016)
This chapter identifies key challenges for universities and the higher-education sector in Africa south of the Sahara (SSA) and, more specifically, explores trends in African faculties of agriculture and their impact on postgraduate training programs. Selected mechanisms by faculties of agriculture and educational networks to respond to the identified challenges are presented and implications of the current trends within the selected faculties are discussed. Finally, the chapter provides lessons and recommendations for improving the quality of postgraduate programs at African faculties.